1979
DOI: 10.1016/s0022-328x(00)92371-4
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of organosilver(I) compounds, and their application in organic synthesis

Abstract: SummaryThe favourable influence of lithium bromide on the thermal stability of organosilver( I) compounds is described. The stabilized silver(I) compounds have been brought into reaction with conjugated enynes; the regiochemistry of the reactions appears to depend on steric factors. A comparison is presented of the behaviour of the silver(I) and the corresponding copper(I) reagents in this reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Dimethylargentate is stable in the gas phase, and has been isolated for short periods (10 s) without significant decomposition. 10 Alkylsilver compounds have been prepared by treatment of Grignard reagents with silver salts, [11][12][13][14][15][16][17][18][19] and similarly undergo oxidative homocoupling to give alkyl dimers. [11][12][13]19,20 Exploitation of this finding has resulted in the development of general methodology for silver-catalyzed alkyl-alkyl homocoupling of Grignard reagents (Table 1.1).…”
Section: Synthesis Stability and Reactivity Of Alkylsilver Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dimethylargentate is stable in the gas phase, and has been isolated for short periods (10 s) without significant decomposition. 10 Alkylsilver compounds have been prepared by treatment of Grignard reagents with silver salts, [11][12][13][14][15][16][17][18][19] and similarly undergo oxidative homocoupling to give alkyl dimers. [11][12][13]19,20 Exploitation of this finding has resulted in the development of general methodology for silver-catalyzed alkyl-alkyl homocoupling of Grignard reagents (Table 1.1).…”
Section: Synthesis Stability and Reactivity Of Alkylsilver Compoundsmentioning
confidence: 99%
“…28 The addition of lithium bromide significantly increases the thermal stability of alkylsilver compounds. 14 Westmijze and coworkers found that the reaction of nbutylmagnesium bromide, for example, with AgBrÁ2LiBr gave a solution of butylsilver that was stable up to À10 C, which is in stark contrast to the species obtained from the reaction with silver bromide alone, which decomposes at À60 C. This marked stabilization of the alkylsilver compounds allowed for the first meaningful use of these reagents in intermolecular reactions.…”
Section: Synthesis Stability and Reactivity Of Alkylsilver Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction of AgCF(CF 3 ) 2 with O 2 , for example, gives hexafluoroacetone. Thermal decomposition generally occurs at temperatures under 100 • C. It was reported that bis(trifluoromethyl)ketene reacts with AgF to produce the perfluoroaldehyde complex AgC(CF 3 ) 2 C(O)F. 40 Excess alkali or alkaline earth halides can suppress thermal decomposition of organosilver compounds. Thus butylsilver, formed from AgBr·2LiBr using Grignard or alkyllithium reagents, decomposes at −10 • C compared with the −60 • C decomposition temperature of the nonstabilized species.…”
Section: Stabilized Organosilver Compoundsmentioning
confidence: 99%
“…Although the role of KF is not clear at this stage, KF would dissociate the aggregation of AgBr or stabilize alkylsilver intermediates by coordination to the silver metal. 11 The silver-catalyzed alkylation reactions (10 mol % AgBr/KF) of various substrates are summarized in Table 2. 12 Both cyclic and acyclic secondary alkyl bromides underwent the alkylation reactions (Table 2, entries 1-4).…”
mentioning
confidence: 99%